Effect of dietary red grape pomace on growth performance, hematology, serum biochemistry, and meat quality parameters in Hy-line Silver Brown cockerels. - Ontiretse Jonathan (Public Library of Science (PLoS), 2021)
Red grape (Vitis vinifera L.) pomace's (RGP) beneficial bioactive compounds could improve growth and meat quality traits in chickens and thus valorize RGP waste that is usually disposed in landfills to the detriment of the environment. This study investigated the effect of RGP inclusion in diets of Hy-line Silver Brown cockerels on physiological and meat quality responses. Five isonitrogenous and isocaloric diets were formulated by mixing a standard grower diet with RGP at 0 (G0), 15 (G15), 30 (G30), 45 (G45) and 60 g/kg (G60). A total of 250, 5-week-old cockerels (304.6 ± 6.57 g live-weight) were evenly allocated to 25 pens replicated 5 times per experimental diet. No linear and quadratic trends (P > 0.05) were observed for overall feed intake, body weight gain, feed conversion ratio, and meat quality traits as dietary RGP levels increased. Erythrocytes linearly decreased (P < 0.05), whereas mean corpuscular hemoglobin and urea linearly increased (P < 0.05) with RGP levels. There were significant quadratic effects for glucose, phosphorus, total protein, albumin, globulin, and cholesterol, from which a maximum RGP inclusion level was calculated to be 43 g/kg. In conclusion, dietary red grape pomace had no adverse effect on physiological parameters and meat quality traits of Hy-line Silver Brown cockerels. However, including red grape pomace beyond 43 g/kg could compromise serum biochemical parameters of the birds.